Serum exosomal microRNA-34a as a potential biomarker in epithelial ovarian cancer - Kazuya Maeda; Hiroshi Sasaki; Shoko Ueda; Shunsuke Miyamoto; Shinichi Terada; Hiromi Konishi; Yuhei Kogata; Keisuke Ashihara; Satoe Fujiwara; Yoshimichi Tanaka; Tomohito Tanaka; Masami Hayashi; et al. (BMC, 2020)
Abstract Background Ovarian cancer (OC) is a leading cause of cancer-related death in women, and thus an accurate diagnosis of the predisposition and its early detection is necessary. The aims of this study were to determine whether serum exosomal microRNA-34a (miR-34a) in ovarian cancer could be used as a potential biomarker. Methods Exosomes from OC patients' serum were collected, and exosomal miRNAs were extracted. The relative expression of miR-34a was calculated from 58 OC samples by quantitative real-time polymerase chain reaction. Results Serum exosomal miR-34a levels were significantly increased in early-stage OC patients compared with advanced-stage patients. Its levels were significantly lower in patients with lymph node metastasis than in those with no lymph node metastasis. Furthermore, its levels in the recurrence group were significantly lower than those in the recurrence-free group. Conclusions Serum exosomal miR-34a could be a potential biomarker for improving the diagnostic efficiency of OC.